Biological Systems Analysis (2005)
Disclosed are methods for the practice of systems pharmacology, systems toxicology, and systems pathology using patterns, such as images, reflective of the biological state of subjects such as humans or experimental mammals. The patterns are generated from data obtained from one or more samples from one or more subjects by applying certain data treatment techniques, and are reflective of the biochemistry of the subjects. The patterns are used in drug selection and discovery, assessment of toxicity and drug efficacy, segmentation of populations, discovery of disease subtypes, as surrogate end points, in the assessment of therapeutic options, and for diagnosis and prognosis of disease.